Irrigation potential in Nigeria: Some perspectives based on factor endowments, tropical nature, and patterns in favorable areas - Takeshima, Hiroyuki; Adesugba, Margaret Abiodun (International Food Policy Research Institute, 2014)
In this paper, we briefly explore these three perspectives that can be useful in the future assessment of irrigation potential in Nigeria: (1) factor endowments, (2) challenges inherent in the tropics, and (3) experiences in a favorable area within Nigeria.